Accumulation, chemical speciation and ecological risks of heavy metals on expanded polystyrene microplastics in seawater - Xie, Qun; Li, Hengxiang; Li, Zhenliang; Zhang, Haiting; Yuan, Minqing; Wu, Minfu; Li, Huawei; Xu, Xiangrong (Gondwana research, 2022)
[Display omitted] •Accumulation of heavy metals on the MPs fitted to a pseudo first-order kinetics.•Cu, Zn, Cd, and Ni on MPs were primarily distributed in the acid soluble fraction.•Pb and As primarily occur in the reducible fraction.•Mobility and bioavailability of metals on MPs ware higher than those in sediments.•The ecological risks of heavy metals on the MPs increase over exposure time. Expanded polystyrene (EPS) microplastics (MPs) have become a major component of plastic debris both on land and in marine systems globally. However, the accumulation and speciation distribution of heavy metals on EPS MPs and their potential hazards to marine organisms are still unknown. In this study, a 12-month field experiment investigating EPS exposure to seawater was conducted, and concentrations and speciation of six heavy metals (Cu, Zn, Cd, Pb, As, and Ni) on the EPS MPs were studied along with an evaluation of their ecological risks. Results showed that the accumulation of heavy metals on the EPS MPs increased over the exposure time, which conformed to a pseudo first-order kinetic equation. Speciation analysis suggested that Cu, Zn, Cd, and Ni principally distributed in the acid soluble fraction, while Pb and As primarily existed in the reducible fraction. There were significant correlations among the reducible fraction, the oxidizable fraction, the residual fraction, and the carbonyl index (p < 0.05). Compared with heavy metals in sediments, the migration and bioavailability of heavy metals on the aged EPS MPs were higher. By comprehensively considering the accumulation amount, chemical speciation and toxicity, the risk levels of heavy metals on the EPS MPs were in the decreasing orders of Cd > Pb > As > Ni > Cu > Zn. The ecological risk of heavy metals on the EPS MPs increased over the exposure time, and Cd, Pb, As, and Ni were the primary contributing factors. Our study results will be helpful for better understanding the ecological risk level of heavy metals on MPs, and will provide a reference for further research on the ecological toxicity of MPs.